Decomposing Recruitment Elasticity in Job Matching - Ryo Kambayashi; Kohei Kawaguchi; Suguru Otani (Institute of Labor Economics (IZA), 2025)
This study estimates and decomposes recruitment elasticity, a key measure of employer market power, across job-matching stages using data from Japan's largest job-matching intermediary. On average, recruitment elasticity is negative but not statistically significantly different from zero. However, this masks heterogeneity across stages. The negative elasticity arises from lower-wage workers avoiding higher-wage vacancies during inquiry. Posted wages positively influence application, interview attendance, and offer acceptance decisions, with elasticity decreasing in that order. Other important patterns are also examined.
Keywords: J20; J30; J42; J64; L13; L40; 330; market power of employers; monopsony; job matching intermediary; recruitment elasticity; inquiry; application; interview; offer; control function approach